3S+2=12-2s

Simple and best practice solution for 3S+2=12-2s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3S+2=12-2s equation:


Simplifying
3S + 2 = 12 + -2s

Reorder the terms:
2 + 3S = 12 + -2s

Solving
2 + 3S = 12 + -2s

Solving for variable 'S'.

Move all terms containing S to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 3S = 12 + -2 + -2s

Combine like terms: 2 + -2 = 0
0 + 3S = 12 + -2 + -2s
3S = 12 + -2 + -2s

Combine like terms: 12 + -2 = 10
3S = 10 + -2s

Divide each side by '3'.
S = 3.333333333 + -0.6666666667s

Simplifying
S = 3.333333333 + -0.6666666667s

See similar equations:

| 5+2m=3+m | | 4a+1=a+7 | | 3t^3-24t+36=0 | | 3x-27=2x+29 | | 5m-8=2m+1 | | 3(z-4)=-6 | | 2a-3y= | | 2(a-5)=-2 | | 4d-7=21 | | 10y=3zx+1 | | a=5i-3j+3k | | F(x)=-x^3+12x+4 | | 5ln(x^2)=0 | | (6x)^5/(3x) | | (6x)^5/(12x) | | 1+x^20=0.5 | | 5z+8=3z+16 | | 5(p+2)-(p+4)=3p-1 | | 3m+3=15-m | | 50/0.15 | | -4(y-2)=-8 | | 4(a+2)=-4 | | 12x+9x=15 | | .25(3x+12)+2x=-5(.25x+3) | | 2sin(2x-10)=1.2516 | | 2u-20=14 | | y=xp^2+p^2 | | 5x+132=6x-21+7x-1 | | (x+3)(x-9)(6-x)=0 | | x^2-x-1+3i=0 | | 3x+(2-4x)=4 | | 8/21k=1/3 |

Equations solver categories